2012
DOI: 10.1123/jab.28.4.431
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Ballistic and Nonballistic Lower-Body Resistance Exercise and the Methods Used to Identify Their Positive Lifting Phases

Abstract: This study compared differences between ballistic jump squat (B) and nonballistic back squat (NB) force, velocity, power, and relative acceleration duration, and the effect that the method used to identify the positive lifting phase had on these parameters. Ground reaction force and barbell kinematics were recorded from 30 resistance trained men during B and NB performance with 45% 1RM. Force, velocity, and power was averaged over positive lifting phases identified using the traditional peak barbell displaceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 23 publications
6
37
0
Order By: Relevance
“…Impulse was obtained from the area under the net GRF-time curve (GRF minus barbell-andbody weight) during the propulsion phase using the trapezoid rule. The propulsion phase was identified from the velocity-time curve and began at the post countermovement transition from negative to positive velocity and ended at peak velocity (9,19). The dependent variables demonstrated high within session testretest reliability with intraclass correlation values between r = 0.902 and 0.970.…”
Section: Discussionmentioning
confidence: 99%
“…Impulse was obtained from the area under the net GRF-time curve (GRF minus barbell-andbody weight) during the propulsion phase using the trapezoid rule. The propulsion phase was identified from the velocity-time curve and began at the post countermovement transition from negative to positive velocity and ended at peak velocity (9,19). The dependent variables demonstrated high within session testretest reliability with intraclass correlation values between r = 0.902 and 0.970.…”
Section: Discussionmentioning
confidence: 99%
“…Peak power was identified as the highest instantaneous value during the propulsion phases of the first pull, second pull and jerk/push-press, whereas mean power was obtained by averaging power over each propulsive phase. The propulsive phases were identified from the velocitytime curve and began from the start of the lift to peak velocity for the first pull and from the post-countermovement transition from negative to positive velocity to peak velocity for the second pull and jerk phases [19][20][21]. Power was calculated as the product of ground reaction force and bar/log velocity.…”
Section: Instrumentationmentioning
confidence: 99%
“…The frequent "one-on-one" SSG-related playing situations involve dynamic actions such as accelerations, decelerations, change of directions, and jumps. These actions are ballistic in nature and previous research has indicated that ballistic movements produce greater muscle and power outputs than non-ballistic ones (Newton et al, 1997;Lake et al, 2012). As a consequence, they may have induced activation of high-threshold motor units, which have been proposed to underline the PAP (Tillin and Bishop, 2009).…”
Section: Lower Bodymentioning
confidence: 99%